2002
DOI: 10.1046/j.1432-1033.2002.02773.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of protein‐3 induces an uncontrolled uncoupling of mitochondria after expression in muscle derived L6 cells

Abstract: The uncoupling proteins (UCPs) are thought to uncouple oxidative phosphorylation in the mitochondria and thus generate heat. One of the UCP isoforms, UCP3, is abundantly expressed in skeletal muscle, the major thermogenic tissue in humans. UCP3 has been overexpressed at high levels in yeast systems, where it leads to the uncoupling of cell respiration, suggesting that UCP3 may indeed be capable of dissipating the mitochondrial proton gradient. This effect, however, was recently shown to be a consequence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…It is argued that the uncoupling effect of UCP may be due to a gain of function of artifacts under overexpression. 44 We have different lines of founder mice that express different levels of UCP2. Two lines of mice with significant differences in UCP2 show similar phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that the uncoupling effect of UCP may be due to a gain of function of artifacts under overexpression. 44 We have different lines of founder mice that express different levels of UCP2. Two lines of mice with significant differences in UCP2 show similar phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This artifact results in an activity of the protein in the basal state (i.e., without activation by fatty acids) that is not inhibited by purine nucleotides when studied in isolated To see all the spots of endogenous UCP2, the blot had to be exposed for 10 min instead of 2 min for the other data mitochondria [32]. In the present study, the lack of uncoupling in the basal conditions, indicated by similar mitochondrial membrane potential, oxygen consumption, and ATP/ADP ratio is an indirect indication that the insertion of UCP1 and UCP2 in the mitochondrial membrane is not causing nonspecific proton leaks.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, UCP2 expression induced by 50 MOI of Ad-UCP2 was quantitatively similar to the endogenously expressed level of UCP2 induced by 15 mM glucose (data not shown). It was previously suggested that if overexpressed UCP3 protein in the mitochondria could be eluted by high concentrations of nonionic detergents, such as Triton X-100, the protein would be functionally active (Guerini et al 2002). Therefore, we applied this concept in our system where UCP2 is overexpressed in INS-1 or native -cells.…”
Section: Intentional Shp Overexpression Does Not Modify the Level Of mentioning
confidence: 99%